2019
DOI: 10.3389/fped.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Nutrition, Growth, and Metabolism in Preterm Infants

Abstract: Biological differences between the sexes are apparent even from the early part of the pregnancy. The crown-rump length is larger in male fetuses compared to females in the first trimester. Placentae of male and female fetuses have different protein and gene expressions, especially in adverse conditions. Even within the intrauterine milieu, the same extracellular micro RNA may show upregulation in females and downregulation in male fetuses. There appears to be a natural survival advantage for females. Maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 75 publications
9
83
0
3
Order By: Relevance
“…Sex differences in metabolism and growth are wellrecognized, starting from conception and lasting through all stages of life [11]. Crown-rump length and biparietal diameter in human male fetuses are larger than in females starting at the first measurement between the 8th and 12th weeks [12].…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in metabolism and growth are wellrecognized, starting from conception and lasting through all stages of life [11]. Crown-rump length and biparietal diameter in human male fetuses are larger than in females starting at the first measurement between the 8th and 12th weeks [12].…”
Section: Discussionmentioning
confidence: 99%
“…There was an even sex distribution in this study sample with a male to female ratio of approximately 9:11. The sex differences observed at birth were consistent with those in the literature (Alur, 2019). Our high-risk cohort had a higher birth weight than the reference population and this may have had consequences for the distribution of childhood adiposity.…”
Section: Sample Makeupsupporting
confidence: 90%
“…In the study conducted by Tusi et al, gender did not have any signi cant relationship with birth weight, height and head circumference. Furthermore, in the study conducted by Ali Malayeri (Jodipour) et al, in Sistan, the weight difference between male and female newborns was not statistically signi cant [13,15]. These ndings are not in line with WHO reports and several other studies that suggested that female newborns were at the risk of underweight [16,17].…”
Section: Discussionmentioning
confidence: 84%